Accidental Displacement of Dental Implants Into Both Maxillary Sinuses During Surgery - Eltas, Abubekir; Dundar, Serkan; Eltas, Seydanur Dengizek; Altun, Oguzhan; Yolcu, Umit; Saybak, Arif (Allen Press Inc, 2015)
[Abstract Not Available]
Keywords: Foreign-Body; Sinusitis; Removal